USE OF MODERN TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING IN SCHOOLS (ResearchJet Journal of Analysis and Inventions, 2020)
The article discusses effective ways to teach a foreign language in schools, innovative teaching technologies. The quality of the lesson depends on the teacher's interest in the lesson, his ability to focus and share his knowledge. The teacher's passion and style are very important in the lesson